In Pursuit of Good Food II: Localized Strategies for School Food Reform at the Boston Arts Academy. - Brown, Brytanee.; Gregg, Catie.; Kravet, Emma. (Tufts University. Tisch Library., 2018)
2012 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Boston Arts Academy. This project is part of the Office of Sustainability Student Project Database, a place to share and view student projects related to sustainability and the environment.